2000
DOI: 10.1046/j.1365-2958.2000.01699.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and transcriptional regulation of ompT, a ToxR‐repressed gene in Vibrio cholerae

Abstract: SummaryIn pathogenic Vibrio cholerae, at least 17 genes are co-ordinately regulated by ToxR. Most of these genes, including those that encode cholera toxin (CT), toxin co-regulated pilus (TCP), accessory colonization factor (ACF) and OmpU, are positively regulated. OmpT is the only identi®ed protein under negative regulation of ToxR. To understand the molecular mechanism by which ToxR represses OmpT expression, we cloned ompT and characterized the ompT promoter and its interaction with ToxR. Sequence analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
114
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 98 publications
(121 citation statements)
references
References 52 publications
(79 reference statements)
6
114
0
1
Order By: Relevance
“…We have shown previously that ToxR binds directly to the -30 to -95 region of the ompT promoter, consistent with its role as a repressor. We also observed sequencedependent activation of ompT transcription in the absence of ToxR and suggested that cAMP receptor protein (CRP) positively regulates ompT transcription (Li et al, 2000). However, how ToxR represses transcription by binding to this site and how ToxR as well as CRP mediate regulated expression of OmpT in response to environmental signals remained to be determined.…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…We have shown previously that ToxR binds directly to the -30 to -95 region of the ompT promoter, consistent with its role as a repressor. We also observed sequencedependent activation of ompT transcription in the absence of ToxR and suggested that cAMP receptor protein (CRP) positively regulates ompT transcription (Li et al, 2000). However, how ToxR represses transcription by binding to this site and how ToxR as well as CRP mediate regulated expression of OmpT in response to environmental signals remained to be determined.…”
Section: Introductionmentioning
confidence: 86%
“…1A, in LB). Our previous observation that CRP is a potential activator of ompT gene expression implies that CRP may contribute to the upregulation of OmpT in response to certain environmental signals (Li et al, 2000). To define the optimal conditions for OmpT expression so that the contribution of CRP as an activator can be assessed, we grew V. cholerae classical strain 395 to different growth phases in rich or minimal media, varying the osmolarity and temperature.…”
Section: Regulation Of Ompt Expression By Environmental Signalsmentioning
confidence: 99%
See 3 more Smart Citations